Peppermint Outperforms Lavender for Post-Cesarean Nausea: A Randomized Controlled Trial - José, Paola Maria; Valentina, Charlotte Amelia; Chloe , Harper Evelyn (Global Indonesia Health Care (GOICARE), 2026)
Background: Many women undergoing cesarean delivery still experience early postoperative nausea and vomiting, even with standard preventive measures. There is limited direct comparative evidence regarding the efficacy of inhaled essential oils when used in addition to routine care, making it unclear which common oil is most effective. Purpose: This study compared the effects of inhaling peppermint versus lavender on postoperative nausea and vomiting within 24 hours in women who had a C-section. Methods: We conducted an RCT at an obstetric center (March–May 2025) enrolling 124 adults; those with essential-oil allergy or unable to consent were excluded. Participants used personal aromasticks with 100% peppermint or 100% lavender at scheduled and as-needed times. The primary outcome was 24-hour PONV. Adjusted regression models estimated risk ratios controlling for age, BMI, parity, prior PONV/motion sickness, anesthesia, opioid/antiemetic use, surgery duration, and blood loss, with prespecified sensitivity, subgroup, and time-to-event analyses. Results: Among 124 participants (mean age ≈31 years), composite PONV occurred in 28.2% (peppermint) versus 45.2% (lavender). Peppermint was associated with lower composite PONV (aRR 0.62, 95% CI 0.41–0.92) and reduced vomiting/retching (aRR 0.50, 95% CI 0.25–0.99) and rescue antiemetic use (aRR 0.57, 95% CI 0.36–0.90). Nausea severity was lower (VAS Δ −0.90; RINVR Δ −1.6), and time to first rescue was prolonged (HR 0.58, 95% CI 0.36–0.94). Results were consistent across sensitivity and subgroup analyses, indicating robustness. Conclusion: Peppermint inhalation significantly reduced early postoperative nausea and vomiting in women after C-sections compared to lavender. This suggests peppermint could be widely adopted in similar obstetric settings, warranting further large-scale studies on its long-term effectiveness, safety, cost, equity, and optimal administration. Relevance to clinical practice: Peppermint aromastick inhalation is a low-cost, nurse-deliverable adjunct to prophylaxis that reduces early PONV and rescue antiemetic use after cesarean delivery, improving comfort and potentially shortening recovery and hospital stay.